A presunção de inocência como "verdade" inicial do processo penal democrático: delimitação da aplicação do princípio no direito brasileiro - Oliveira, Bruno Massing de (2018)
The present study deals with the delimitation of the application of the principle of presumption of innocence in the Brazilian criminal procedure, that is, at what moment the guarantee begins to produce its effects and at what point it stops them from producing. It mentions, initially, the role of the legal principles for a democratic state of law, the role of the principles of criminal procedure in criminal proceedings, the evolution of the principle of the presumption of innocence during procedural systems and the presumption of innocence must be understood in order to maximize the effectiveness of this fundamental right. Then, in a second moment of the research, it highlights the functions of presumption of innocence, as “probative norm”, “norm of judgment” and “norm of treatment”. In order to do so, it examines the activity of the magistrate in the management of evidence, the burden of proof in criminal proceedings, as the judge must decide the criminal case if the facts alleged by the prosecution are not proven and the procedural arrest as a means provided in the legal system to exclude the presumption of innocence. It analyzes the effects of the presumption of innocence during the administrative acts, during the preliminary investigation acts and other pre-procedural acts, during the criminal proceedings and during the execution of the sentence. In the end, the research concludes that the essencial nucleus of the presumption of innocence ranges from administrative acts to the final res judicata, where the guarantee must act to limit the power of the state.